Handwashing and contamination of stethoscopes in two hospitals in Huánuco, Perú - Ramos-Cardozo, Andrés (2020)
Introduction: The stethoscope is the universal tool for the physician and the medical staff, it is in direct contact with numerous patients and it is a possible vector of infections associated with health care. The present study sought to determine the association of hand washing and the cleaning of stethoscopes with their contamination, Methods: We conducted an observational, descriptive and cross-sectional study. Diaphragm samples of 70 stethoscopes were cultured and a questionnaire was applied to the medical staff who used them. Results: The contamination of stethoscopes was 90% and the most frequent microorganism was coagulase negative Staphylococcus. In the bivariate analysis, a significant association was found between the contamination of stethoscopes, the absence of hand washing, and the frequency of cleaning less than ten times a month. Conclusion: Handwashing and cleaning the stethoscope more than 10 times a month are protective factors to avoid contamination of stethoscopes.